Implementation of the two-ways symmetrical model of grunig and hunt on the performance of public relations of the geological agency in disaster mitigation in West Java: English and Indonesian - Tresnoati, Widia Sari (Privietlab, 2026)
West Java is one of the areas in Indonesia that is most likely to experience geological disasters. This means that government agencies and the community must communicate risks clearly and effectively. In this case, the Geological Agency plays a key role in providing scientific data and distributing disaster mitigation information through its public relations function. This study aims to examine the application of the Two-Way Symmetric Model of communication in the performance of the Public Relations Unit of the Geological Agency in disaster mitigation efforts in West Java, Indonesia. In particular, this study explores the forms of communication applied, the role of symmetrical communication in building public trust and participation, and the supporting and inhibiting factors that influence its implementation. This study adopted a qualitative approach. Data were collected through field observations, comprehensive interviews with Geological Agency Public Relations personnel, and documentation studies derived from press-release manuscripts, social media content, and institutional communication materials related to disaster mitigation. Interactive models that include data reduction, data presentation, and conclusion drawing are used to evaluate the data. Triangulation of sources and methods is used to ensure the validity of the research. The results of the study show that the Public Relations of the Geological Agency has begun to use two-way symmetrical communication by mixing formal communication channels, such as press releases, and collaborating with government agencies, with informal and digital media that allow the public to provide feedback. This method helps build public trust and involves people in disaster relief initiatives, especially when the material is easy to understand and there are opportunities for people to talk about it. However, the application of symmetrical communication is still partial and situational. This is due to the bureaucratic structure, lack of communication resources, and the fact that technocratic techniques are often used to write messages. Research shows that strengthening institutional commitments, improving communication capabilities, and incorporating public input into strategic decision-making are critical for maximizing the application of the Two-Way Symmetric Model in disaster mitigation communication.